A Web Map Service for Mobile Computers - Davis Jr., Clodoveu A.; Kimo, Yuri Jorge; Duarte-Figueiredo, Fátima L. P. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2009: Anais do XXXVI Seminário Integrado de Software e Hardware, 2009)
One of the Grand Challenges for computing today involves providing access to large volumes of distributed multimedia data. Mapping and personal navigation are among the most interesting applications involving this challenge, since they require access to large volumes of data, both static (such as street maps) and dynamic (such as traffic conditions). Such applications are currently the focus of much attention, considering that hardware is improving and wireless networks are becoming ubiquitous. Access to online maps is mainly done nowadays through proprietary and thematically limited geographic information services, such as Google Maps. A more interesting alternative for Web-based map access is to use data sources from spatial data infrastructures based on the Open Geospatial Consortium’s standardized Web services, such as the Web Map Service (WMS). WMS, however, imposes a higher communications overhead and power consumption to the mobile device, and has a limited scalability potential. This paper presents a proposal for the a WMS client architecture that presents significant gains over the current approach, especially regarding the data transmission overhead imposed by OGC Web services.